Populist Radical Right Parties' Impact on European Foreign Aid Spending - Christine Hackenesch; Maximilian Högl; Hannes Öhler; Aline Burni (JCMS: Journal of Common Market Studies, 2022)
Since the early 2000s, populist radical right parties (PRRPs) have more than doubled their electoral support in Europe. Previous research found that PRRPs impact migration policy. However, little is known about whether they also impact other fields of domestic and foreign policy. Using a cross-country panel analysis, we test to what extent the rise of PRRPs has influenced European foreign aid spending. We find that while the rise of PRRPs has not been associated with an overall reduction in foreign aid, it has led to changes in how aid moneys are spent. PRRP strength is linked to a higher share of aid for migration-containment objectives, and less aid for addressing climate change and for multilateral organizations. Our analysis thereby provides evidence that the `electoral threat' of PRRPs puts mainstream parties under pressure not only with regard to migration but also in relation to the climate–development nexus and aid for multilateralism.
Keywords: 330; populist radical right parties; foreign aid; migration; climate change; Europe